Burden of Systemic Lupus Erythematosus on Work Productivity and Daily Living Activity: A Cross-Sectional Study Among Malaysian Multi-Ethnic Cohort - Fakhriah ABU BAKAR,; Syahrul SAZLIYANA SHAHARIR,; Rozita MOHD,; Mohd Shahrir MOHAMED SAID,; Sakthiswary RAJALINGHAM,; Kong WEI YEN, (Archives of Rheumatology, 2020)
Objectives: This study aims to assess the self-reported work productivity and activity daily living (ADL) impairment among Malaysian patients with systemic lupus erythematosus (SLE) and to examine their associated factors. Patients and methods: This cross-sectional study included 167 SLE patients (21 males, 146 females; mean age 38.2±9.8 years; range, 20 to 60 years) recruited from the outpatient Rheumatology and Nephrology clinics. Face-to-face interviews were conducted to record patients’ socio- demographics (age, sex, ethnicity, marital status, and occupation) and SLE disease characteristics (system involvement, age onset, and presence of organ damage). Disease activity was assessed using the Systemic Lupus Erythematosus Disease Activity Index-2000 (SLEDAI-2K). Short form 36 (SF-36) was used to determine health-related quality of life (HRQoL) while Work Productivity and Activity Impairment (WPAI) questionnaire was used to assess the four domains of absenteeism, presenteeism, overall work productivity, and non-work related ADL impairment. Univariate analyses and multivariable regression analysis examined the association of demographic variables, SLE disease characteristics, and activity with reduced HRQoL and WPAI scores. Results: The majority of the patients were Malays (59.3%), followed by Chinese (34.7%) and Indian (3.6%) patients. More than two-thirds of the patients reported some degree of impairment in their work productivity and ADL due to the disease. The absenteeism rate was 10.4% in the past one week and their indirect costs were 2,875.17 Malaysian ringgits (US $701.22) in the past seven days. Significant predictors of higher work productivity and ADL impairment scores were higher disease activity, more frequent SLE flares, lupus nephritis, and hematological involvement of SLE. Patients with higher work productivity and ADL impairment scores were also strongly associated with poor QoL. No ethnic disparities of work productivity and ADL impairment were found. Conclusion: Systemic lupus erythematosus significantly affected the overall productivity in work and non-work related activity in our Malaysian multi-ethnic cohort and both impairments were significantly associated with poor QoL.